Construction Noise Pollution and Worker Perceptions in Kohalpur Municipality: Exposure Levels, Health Risks, and Control Gaps - Shahi, Sushila; Neupane, Uttam; Chauhan, Raju; Rijal, Bidya (Himalayan Journal of Applied Science and Engineering, 2025)
Occupational noise exposure in construction sites is a growing concern for workers’ health and safety. This case study assesses noise levels in Kohalpur Municipality, Nepal, and explores workers’ awareness, perceptions, and use of protective measures. A mixed-methods approach was used, combining field measurements with the Decibel X mobile app, structured questionnaires, and secondary data analysis using SPSS and Excel. Results show that noise from construction equipment often exceeds recommended exposure limits, particularly at high frequencies. Despite the risks of hearing loss, stress, and reduced productivity, 100% of respondents reported no training, and 87.3% indicated a lack of noise control measures. Most employers do not provide hearing protection or conduct noise monitoring. The findings highlight the urgent need for awareness programs, enforcement of noise regulations, and implementation of control strategies to protect workers’ health and enhance safety in the construction sector.